Sistem Penilaian Sidang Skripsi Berbasis Website - Endy Syaiful Alim; Rahmi Imanda; E Erizal; Arafat Febriandirza; Muhammad Solehuddin Al-Khawarizmi (LPPM STIKOM Tunas Bangsa, 2023)
Currently, the assessment system and trial registration at the Faculty of Engineering Uhamka is still done manually with the help of google forms for trial registration and Excel files for trial assessments. The flow of the file delivery process, which is still conventional, also causes delays in the trial assessment process. This research aims to create a management information system that regulates the thesis trial registration process, assessment, and the process of sending the required files. The assessment system for the thesis trial was made using the prototype method. Starting from collecting and analyzing data through interviews and questionnaires, designing use case diagrams and mockups, and implementing. The making of this website is focused on the registration of thesis examinations for students and the assessment of thesis examinations for lecturers.